Journal of the operational research society - Operational Research Society (Great Britain) (Oxford, England ; New York : Published by Pergamon Press for Operational Research Society, 1978)
Access available online from 2008-
Published: Houndmills, Basington, England : Stockton Press for Operational Research Society, 1997-
Title from cover.
Keywords: Operations research -- Periodicals; Operations research